MEASURING THE EXISTENCE OF ACEH'S LOCAL PARTIES IN ACEH LEGISLATIVE ELECTION 2009-2019 - Syarkawi Syarkawi; Hendri Koeswara; Desna Aromatica (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2021)
This study aims to determine the existence of local political parties in Aceh in the 2009-2019 legislative elections. The presence of local political parties in Aceh is a the result of the peace conflict between the Free Aceh Movement (GAM) and the Government Republic of Indonesia. The birth of a local political party in Aceh brought considerable influence large in the control of seats in the parliament in Aceh in its first participation in the 2009 legislative elections. However, his presence continues to experience According to him, the decline was in line with the number of votes in the next legislative election. This study aims to measure the existence of local political parties in Aceh in terms of 2009-2019 legislative elections. The research method uses the method qualitative descriptive with research focus on legislative elections at the provincial level Aceh in 2009-2019. The data collection techniques used are: interviews and documentation studies. The results showed that the existence of the party Aceh's local politics continues to decline as the number of votes and local political party seats in the 2014 and 2019 legislative elections when compared to the 2009 legislative elections. The decline in the existence of parties local politics in Aceh is measured from the concept of systemic degree, value identity, degree of autonomy and public knowledge